Antibiogram and phage typing of Staphylococcus aureus isolated from meat, fish and food handlers - DAS, S C; KHANNA, P N (The Indian Journal of Animal Sciences, 2013)
Of the 180 samples of meat (68), fish (62) and food handlers (50), 65 (36.11%) were found contaminated with coagulase-positive S. aureus. By antibiogram the highest sensitivity to gentamycin, followed by that of chloramphenicol, ampicillin, erythromycin, streptomycin, penicillin-G ,and oxytctracycline was detected. Bacteriophage typing of 39 isolates revealed that 69.23 and 53.84 % were typahle with human and bovine phages respectively. Most of the bovine isolates were typable with human phages and vice-versa, showing thereby the zoonotic potentiality and public health significance.